The complete book of radio-controlled models how to build and operate model boats, aircraft, cars and trucks - Ellis, Chris (Quarto Book, 1999)
This guide demonstrates how to build, tune and race model cars, boats and planes, ranging from minimum-assembly kits for beginners to custom-made machines for the experienced enthusiast. It includes safety guidelines and hints on how to obtain the best performance from the model vehicle.